Respuesta :
ANSWER
[tex]\sum_{n=1}^53(-2)^{n-1} = 33[/tex]
EXPLANATION
The given series is
[tex]\sum_{n=1}^53(-2)^{n-1} [/tex]
This is a geometric series with general term,
[tex]a_n=3( { - 2)}^{n - 1} [/tex]
The terms are:
[tex]a_1=3( { - 2)}^{1- 1} = 3[/tex]
[tex]a_2=3( { - 2)}^{2- 1} = - 6[/tex]
[tex]a_3=3( { - 2)}^{3- 1} = 12[/tex]
[tex]a_4=3( { - 2)}^{4 - 1} = - 24[/tex]
[tex]a_5=3( { - 2)}^{5- 1} = 48[/tex]
This implies that,
[tex]\sum_{n=1}^53(-2)^{n-1} = 3 + - 6 + 12 + - 24 + 48[/tex]
[tex]\sum_{n=1}^53(-2)^{n-1} = 33[/tex]
Answer: 33
Step-by-step explanation:
I just took the quiz!